Novel and Emerging Drugs for Systemic Lupus Erythematosus: Mechanism of Action and Therapeutic Activity - Robak, E.; Robak, T. (Current Medicinal Chemistry, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by B cell hyperactivity and defective T-cell function, and several cytokine aberrations, with high titer production of autoantibodies and clinical involvement in multiple organ systems. It can present with a wide variety of symptoms, most commonly involving the skin, joints, kidneys, and blood vessels. Patients with mild SLE can be treated with non-steroidal antiinflammatory drugs and antimalarials. Corticosteroids, azathioprine and cyclophosphamide, remain important for long term management of most patients with active disease. In recent years, significant progress in molecular and cellular biology of SLE has resulted in a better characterization and understanding of the biology and prognosis of this disease. These achievements have provided new opportunities for the development of innovative, more effective, therapies. Novel agents potentially useful in the treatment of patients with SLE include tolerogens, monoclonal antibodies and other agents. Tolerogens are synthetic molecules that can bind and cross-link autoantibodies on reactive B-cell surface, promoting B-cell depletion or inactivity. An anti-DNA antibody based peptide, pCons, might have also therapeutic efficacy in SLE patients who are positive for anti-DNA antibodies. In addition, prasterone, a proprietary synthetic dehydroepiandrosterone product is under investigation for the treatment of SLE. Blockade of TLR9 with specific G-rich DNAoligonucleotids also suppresses lupus activity. Several newer mAbs have been developed and are being evaluated in phase I/II clinical trials. These include newer anti-CD20 mAbs, anti-cytokine therapies, anti-BLys mAbs and anti-C5 mAbs. Most of the new agents which could be potentially useful in the treatment of patients with SLE need further laboratory investigations and clinical trials. In this review, promising new agents, potentially useful in SLE, are presented.
Keywords: abetimus